2024
DOI: 10.1161/circulationaha.123.067512
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants for Stroke Prevention in Patients With Device-Detected Atrial Fibrillation: A Study-Level Meta-Analysis of the NOAH-AFNET 6 and ARTESiA Trials

William F. McIntyre,
Alexander P. Benz,
Nina Becher
et al.

Abstract: Background: Device-detected atrial fibrillation (AF) (also known as subclinical AF or atrial high-rate episodes) is a common finding in patients with an implanted cardiac rhythm device and is associated with an increased risk of ischemic stroke. Whether oral anticoagulation is effective and safe in this patient population is unclear. Methods: We performed a systematic review of MEDLINE and Embase for randomized trials comparing oral anticoagulation to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 27 publications
(40 reference statements)
0
47
0
4
Order By: Relevance
“…As with NOAH-AFNET 6, the rate of ischemic stroke was low at only 1.2% per year in the comparator arm, which was also confirmed by a study-level meta-analysis of the 2 trials. 13 Together, LOOP, NOAH-AFNET 6, and ARTESiA confirm that the most common type of AF detected on an ILR—subclinical AF—confers a lower stroke risk and less clear net benefit from OAC compared with clinically diagnosed AF.…”
Section: Novel Insights On Subclinical Afmentioning
confidence: 84%
“…As with NOAH-AFNET 6, the rate of ischemic stroke was low at only 1.2% per year in the comparator arm, which was also confirmed by a study-level meta-analysis of the 2 trials. 13 Together, LOOP, NOAH-AFNET 6, and ARTESiA confirm that the most common type of AF detected on an ILR—subclinical AF—confers a lower stroke risk and less clear net benefit from OAC compared with clinically diagnosed AF.…”
Section: Novel Insights On Subclinical Afmentioning
confidence: 84%
“… 62 , 63 In the study-level meta-analysis of these two trials, there was significant reduction in the rate of ischaemic stroke with OAC [relative risk (RR) 0.68; 95% CI 0.50–0.92, with no sign of heterogeneity) and significant increase in the rate of major bleeding (RR 1.62; 95% CI 1.05–2.5). 67 The duration of AHRE did not interact with the efficacy or safety of anticoagulation, either using the 24-h threshold or as a continuous covariate in the NOAH-AFNET 6 trial. 68 Only 9.4% of included patients had previous stroke/TIA or systemic embolism.…”
Section: Left Atrial Diseasementioning
confidence: 93%
“…The ARTESIA trial (Apixaban for the Reduction of Thrombo-Embolism in Patients with Device-Detected Subclinical Atrial Fibrillation Trial) and concomitant systematic meta-analysis demonstrated a lower risk of stroke or systemic embolism (albeit a higher risk of major bleeding) with oral anticoagulation in patients with SCAF. 9,10 The role of screening for SCAF using left atrial strain or any other imaging approach (as opposed to detecting SCAF with monitoring), however, is unclear. 11,12 In patients with cryptogenic stroke, where the rate of SCAF is likely ≈30%, oral anticoagulation did not decrease the risk of recurrent stroke.…”
Section: See Article By Olsen Et Almentioning
confidence: 99%